Pendekatan Konseling Kognitif Perilaku - Amanullah, Akhmad Syah Roni (STKIP Andi Matappa, 2019)
The cognitive behavioral counseling approach is a comprehensive counseling approach by combining cognitive therapy and behavior therapy approaches. The cognitive behavioral counseling approach basically believes that human thought patterns are formed through the Stimulus-Cognition-Response (SKR) process, which is interconnected and forms a kind of Stimulus-Cognition-Response network in the human brain, where cognitive processes are the decisive factor in explaining how humans think, feel and act . The behavioral counseling cognitive approach has proven to be effective, with 350 studies showing psychiatric and psychological problems ranging from depression to anxiety disorders and personality